1991
DOI: 10.1111/j.1365-3040.1991.tb01521.x
|View full text |Cite
|
Sign up to set email alerts
|

Stomatal responses to humidity in air and helox

Abstract: Abstract. Stomatal responses to humidity were studied in several species using normal air and a helium: oxygen mixture (79:21 v/v, with CO2 and water vapour added), which we termed ‘helox’. Since water vapour diffuses 2.33 times faster in helox than in air, it was possible to vary the water‐vapour concentration difference between the leaf and the air at the leaf surface independently of the transpiration rate and vice versa. The CO2 concentration at the evaporating surfaces (ci), leaf temperature and photon fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
286
1
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 432 publications
(310 citation statements)
references
References 15 publications
19
286
1
4
Order By: Relevance
“…(2) Water flows frotn the xylem to an evaporating site within the leaf. Most proposed feedback meehanisms for stotnatal responses to transpiration rate incorporate the concept of an evaporating site that experiences a reduetion of water potential proportional to the transpiration rate (Sehulze 1994;Mott & Parkhurst 1991). This idea is consistent with pressure probe studies detnonstrating that mesophyll and epidertnal water potentials decrease as the water vapor mole fraction deficit {Aw) is inereased, while xylem water potential stays relatively constant (Nonami & Schulze 1989).…”
Section: Assumptionssupporting
confidence: 66%
“…(2) Water flows frotn the xylem to an evaporating site within the leaf. Most proposed feedback meehanisms for stotnatal responses to transpiration rate incorporate the concept of an evaporating site that experiences a reduetion of water potential proportional to the transpiration rate (Sehulze 1994;Mott & Parkhurst 1991). This idea is consistent with pressure probe studies detnonstrating that mesophyll and epidertnal water potentials decrease as the water vapor mole fraction deficit {Aw) is inereased, while xylem water potential stays relatively constant (Nonami & Schulze 1989).…”
Section: Assumptionssupporting
confidence: 66%
“…Mott & Parkhurst (1991) have demonstrated that the response to humidity may actually be a response to transpiration rate, which provided motivation for the model of Monteith (1995). However, although Mott & Parkhurst (1991) ascribe the feedforward response to 'patchy closure', their experiment was not capable of differentiating between whole-leaf and peristomatal transpiration. Patchy closure cannot be eliminated in the present study because of the apparent change in the A/Q curve with LAVPD.…”
Section: Discussionmentioning
confidence: 99%
“…Trees often regulate their stomatal conductance to maintain a specific transpiration rate across a wide range of VPD. 23 Loblolly pine adjusted g s in this manner but only at a given temperature. When temperature increased transpiration increased as well.…”
Section: Textmentioning
confidence: 99%